(3Yjhf GdJhGQjNs - (3eMeO Hf TGcQ Hf CMeO Hf YHO GdQMef GdcJHj GdOGQGfqj GdOeTbqj, UdGM GdOjf , GHf TGcQ J (B764 (3g` s ((3eMehO UGOb agej Hf GdSjO Cejf GdeGdM s)
(3ChdgG (B:s
(3hHYO adeG cGf Yde GdJGQjN ef CYPH Ydhe GdCOH efHYkG hcfJ eef JYdb ef GdaVd HCghGFg abUOJ Gf CLeY JGQjNkG COhf ajg s
(3BNQgG (B:s
(3heG abO GdeGVhf eKd eMeO hdG eKdg MJi GdbjGeI jabO Udi Gddg Ydjg s
(3GfXQ Qbe (B345 (3, Qbe (B746 (3, Qbe (B6145 (3JGQjNs
(3fSNI YGTQI s
(3hbO cJH GdfGSN GdCLRGA Hjf SfJj (B1328 - 1330 (3g` s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs